The use of lecturer feedback via kahoot! Quiz on pre-service teachersâ referencing skills in academic writing - Kee, Li Li; Razali, Abu Bakar (Malaysian Journal Online, 2021)
The acknowledgment of sources included by pre-service teachers in their academic writing is crucial to be implemented. Additionally, lecturers’ feedbacks are important and a lecturer intervenes at any point in the writing processes is to help the pre-service teachers to produce effective academic writing. Via Kahoot! Quiz, pre-service teachers experience learning by obtaining the immediate feedbacks from their lecturers upon decisions made when partaking in the referencing skills kahoot. As such, this research adopted an action research design on the use of lecturers’ feedbacks via Kahoot! Quiz to improve referencing skills in academic writing among pre-service teachers in an Institute of Teacher Education (ITE). The study was conducted on 16 pre-service teachers in which both quantitative and qualitative data collection methods were employed: (1) pre- and post-referencing skills tests, (2) online Kahoot! Quiz, and (3) students’ work. The mean value for post-referencing skills test is higher (M = 19.06) as compared to the mean value for pre-referencing skills test (M = 11.0). The findings indicate that the use of lecturers’ feedbacks via Kahoot! Quiz does improve pre-service teachers’ referencing skills. It also provides constructive learning environment for pre-service teachers to scaffold, construct, and mould their understanding of referencing skills. The researchers believe that the use of lecturers’ feedbacks via Kahoot! Quiz can be carried out over an extended duration to develop the pre-service teachers’ deeper comprehension of referencing skills in academic writing.